<A multidisciplinary approach to embodiment understanding human being - Dess, Nancy Kimberly 1957- (Advances in theoretical and philosophical psychology, 2021)
"This is a collection of pithy and accessible essays on the nature and implications of human embodiment which explore the concept of 'human being' in the most unprecedented manner through seemingly disparate academic disciplines. With contributions from key researchers from around the world, this book engages with embodiment through the lens of "new materialism". It eschews the view that human beings are debased by materiality and creates a vision of humans as fully embodied creatures situated in a richly populated living planet. The essays in this volume will illustrate and foster new materialist thought in areas including psychology, astrophysics, geology, biology, sociology, philosophy, and the performing arts. The book's engaging and enlightening content is made accessible to readers with relatively little background in the various academic disciplines. This is an important and fascinating text which invites readers to explore and expand their understanding and experience of embodiment. It will be particularly useful for postgraduate students and scholars of theoretical and philosophical psychology, philosophy of the mind, and social and cultural anthropology"--